Analysis of design parameter effects on vibration modes of a motorcycle drum brake and brake shoe using the finite element method - Zahrul, Fuadi; Zaidi, Mohd Ripin (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/